2016
DOI: 10.1177/0886260516662437
|View full text |Cite
|
Sign up to set email alerts
|

Making Judgments: How Blame Mediates the Influence of Rape Myth Acceptance in Police Response to Sexual Assault

Abstract: As research continues to describe negative experiences and high case attrition within sexual assault cases reported to the police, it is important to better understand the role of first-responding police officers. This study surveyed a sample of sworn police officers ( N = 174) from one department in a midsized city in the Great Lakes region to examine the effect of individual police officer characteristics, rape myth acceptance (RMA), attributions of blame, and case characteristics from a hypothetical vignett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 71 publications
(104 reference statements)
1
53
0
4
Order By: Relevance
“…The following inclusion criteria were then applied: the study must include (i) a police officer sample; (ii) a quantitative or qualitative assessment of one of the following attitudes (a) blaming (or responsibility) (b) credibility, or (c) rape myth acceptance; and (iii) original data as opposed to a review or meta-analysis (these criteria were also applied in the following searches). Screening of abstracts and titles resulted in seven studies being extracted: Areh, Mesko, and Umek (2009), Darwinkle, POLICE OFFICER ATTITUDES ABOUT RAPE VICTIMS Powell, and Tidmarsh (2013), Maddox, Lee, and Barker (2013), Sleath and Bull (2012), Rich and Seffrin (2012), Venema (2016) and Wentz and Archbold (2012). As rape victim blaming is often overlapped with attributions of responsibility and these two concepts are conceptually linked (see Shaver, 1985), the above search was completed with the last component being victim respon* to ensure that all blaming and responsibility articles were found.…”
Section: Review Selection Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…The following inclusion criteria were then applied: the study must include (i) a police officer sample; (ii) a quantitative or qualitative assessment of one of the following attitudes (a) blaming (or responsibility) (b) credibility, or (c) rape myth acceptance; and (iii) original data as opposed to a review or meta-analysis (these criteria were also applied in the following searches). Screening of abstracts and titles resulted in seven studies being extracted: Areh, Mesko, and Umek (2009), Darwinkle, POLICE OFFICER ATTITUDES ABOUT RAPE VICTIMS Powell, and Tidmarsh (2013), Maddox, Lee, and Barker (2013), Sleath and Bull (2012), Rich and Seffrin (2012), Venema (2016) and Wentz and Archbold (2012). As rape victim blaming is often overlapped with attributions of responsibility and these two concepts are conceptually linked (see Shaver, 1985), the above search was completed with the last component being victim respon* to ensure that all blaming and responsibility articles were found.…”
Section: Review Selection Methodologymentioning
confidence: 99%
“…This systematic search revealed that the majority of the studies used quantitative methodologies to assess the perception of victims or the acceptance of rape myths. Only five articles solely used qualitative methods (Campbell et al, 2015;Fragoso, 2011;Maddox, Lee, & Barker, 2012 1 ;Venema, 2014Venema, , 2016) with a further two containing a qualitative component (Mennicke et al, 2014;Wentz & Archbold, 2012). The predominant methodology to examine perceptions of victims was use of a vignette of a rape scenario, followed by questions regarding blame and/or credibility, as well as questions that related to police decision making, e.g., decisions to authorise the case, perceptions of guilt (see Table 1 for details).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such research is vital in improving understanding of how officers may evaluate cases of rape in real life, and in establishing which rape-myth-related elements of cases are likely to create variations in said judgments. This is particularly important considering the strong evidence in support of the detrimental effect of negative attitudes on officers' decision making during the investigative process (O'Keeffe, Brown, & Lyons, 2009;Venema, 2016a) and on their evaluations of victim and rape legitimacy (Venema, 2016b). Furthermore, victims' opinions and beliefs about how they feel officers will approach their case has a substantial impact on their decision to report (Jordan, 2001(Jordan, , 2004; for example, between 11% and 26% of victims chose not to report because they believed officers: would not believe them, would not act upon the information, and would not be sympathetic (Office for National Statistics, 2015a; Tjaden & Thoennes, 2000).…”
Section: The Present Studymentioning
confidence: 99%
“…The research on gender biases in charging decisions in civilian jurisdictions for sexual assaults leads us to expect that commanders would routinely fail to take action on sexual assault cases despite compelling evidence (Spohn et al ; Venema ). Officials would view cases through the gendered lens of rape myths (Spohn and Tellis ; Venema ), with victims revictimized and perpetrators seldom held to account (Campbell and Fehler‐Cabral ; Shaw et al ; Venema ). Research on civilian systems has also found that subtle biases do lead victims to report late and withdraw from the subsequent case investigations (Anders and Christopher ).…”
Section: Introductionmentioning
confidence: 99%